Atividades esportivas e estatística básica - Santos Júnior, Melquíades Novaes dos (2017)
The purpose of this paper is to present observations about the use of a Project Descriptive Statistics as a pedagogical strategy for teaching-learning Statistics. In order to provide a more meaningful study and to value the development of statistical skills and thus to a large extent to meet the objectives of Statistical Education. Students aged 14-17 years, from State School Mercedes de Paula Sˆoda, were asked to organize a sports competition with students in the fourth, fifth and sixth years. Such an approach provided a more attractive content and at the same time involved all participants in the process. The objective is to develop in students the ability to investigate data, communicate using statistical terms and give meaning to curricular content through real situations. In the end the material produced as well as student participation will be analyzed and the general impressions on the impact of the Project on the development of statistical skills.